Morphology and functional histology of the lower respiratory system of reticulated python (Malayopython reticulatus) - Benedict, Joash Shane; Chong, Chiu Nie; Mayaki, Abubakar Musa; Mohd Noor, Mohd Akmal; Che' Amat, Azlan; Abdul Razak, Intan Shameha (Institut Biosains, Universiti Putra Malaysia, 2022)
Respiratory tract disease (RTD) is one of the most common syndromes affecting pythons worldwide. Treatments may appear inefficient due to improper knowledge of the anatomy of the system, itself. Moreover, to date, there is no functional histology of reticulated python (RP) reported. Thus, our aim was to provide the histomorphology of the RP lower respiratory system (LRS) in relation to its function. Six (6) RP carcasses were obtained opportunistically for this experiment. The gross anatomy of the LRS organs was measured and recorded before samples were processed accordingly for routine histology. It was observed that the LRS comprised the trachea, lungs, and air sacs with the diaphragm abstinent. The lungs observed were elongated spongy cylindrical structures connected with the diaphanous and hollow air sacs, which interestingly appeared longer on the right side. The lumen was found to be lined by honeycomb appearances of trabeculae. Histologically, the lungs parenchyma comprised the ediculae and faveolae. The air sacs were lined by the pseudostratified ciliated columnar epithelium. The possible functional significance of these structures was also discussed. Thus, this study provides information about the histomorphology of the LRS of RP that could be useful for veterinarians and for future reference.